A Beginner's Guide to Finite Mathematics For Business, Management, and the Social Sciences - Wallis, W.D (Birkhäuser Boston : Imprint: Birkhäuser, 2012)
"The present textbook gives a concise introduction to finite mathematics. It covers the topics counting, discrete probability, graph theory, linear equations, and linear programming...The mathematical level seems higher than the average US textbook on this topic. It is well written and easy to read, with many examples and applications."  -Internationale Mathematische Nachrichten (Review of First Edition)  "This book is designed for an elementary one-semester course in finite mathematics and applications. Finite mathematics here means applicable discrete mathematics used by students in business, management and social sciences...A number of worked examples, called sample problems, are included in the body of each section. Every chapter is closed with a lot of exercises; complete solutions are provided at the end of the book...I would recommend this book [to] everyone who wants to have a first look at applied discrete mathematics."  -Simulation News (Review of First Edition) This second edition of A Beginner's Guide to Finite Mathematics: For Business, Management, and the Social Sciences takes a distinctly applied approach to finite mathematics at the freshman and sophomore level. Topics are presented sequentially: the book opens with a brief review of sets and numbers, followed by an introduction to data sets, histograms, means and medians. Counting techniques and the Binomial Theorem are covered, which provide the foundation for elementary probability theory; this, in turn, leads to basic statistics. This new edition includes chapters on game theory and financial mathematics. Graph theory is defined, with particular emphasis on its use in mathematical modeling. Matrices and vectors are discussed, along with several elementary commercial applications, including linear programming, the theory of games, and financial mathematics. Ample examples and illustrations are provided throughout; each section contains two sets of problems, with solutions provided for the first set. Requiring little mathematical background beyond high school algebra, the text will be especially useful for business and liberal arts majors for study in the classroom or for self-study. Its straightforward treatment of the essential concepts in finite mathematics will appeal to a wide audience of students and teachers.